1997
DOI: 10.1037/0096-1523.23.3.651
|View full text |Cite
|
Sign up to set email alerts
|

Talker identification based on phonetic information.

Abstract: Accounts of the identification of words and talkers commonly rely on different acoustic properties. To identify a word, a perceiver discards acoustic aspects of an utterance that are talker specific, forming an abstract representation of the linguistic message with which to probe a mental lexicon. To identify a talker, a perceiver discards acoustic aspects of an utterance specific to particular phonemes, creating a representation of voice quality with which to search for familiar talkers in long-term memory. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
221
2

Year Published

1998
1998
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 177 publications
(239 citation statements)
references
References 76 publications
14
221
2
Order By: Relevance
“…The study by Remez et al (1997) further showed that these phonetic properties of the sinewaves also preserve talker-specific aspects of speech. In this experiment, sinewave utterances modeled from the natural speech of 10 talkers were presented to listeners in a test of individual recognition.…”
Section: A Common Codementioning
confidence: 99%
See 2 more Smart Citations
“…The study by Remez et al (1997) further showed that these phonetic properties of the sinewaves also preserve talker-specific aspects of speech. In this experiment, sinewave utterances modeled from the natural speech of 10 talkers were presented to listeners in a test of individual recognition.…”
Section: A Common Codementioning
confidence: 99%
“…Because Remez et al (1997) did not manipulate or control a listener's familiarity with the talkers in the test set, it is impossible to know whether the observed variation was due to differences in the degree or quality of familiarity or to other factors in the talker ensemble, such as perceptual distinctiveness or discriminability of the specific samples.…”
Section: A Common Codementioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, Van Lancker, Kreiman, and Emmorey (1985;Van Lancker, Kreiman, & Wickens, 1985) reported that famous voices are easily recognized, even when played backward or when rate compressed. More recently, Remez, Fellowes, and Rubin (1997) found that listeners can identify familiar voices, using only "sinewave sentences" as stimuli.…”
Section: Speaker Normalizationmentioning
confidence: 99%
“…However, the vocal tract length is not an absolute indicator of identity, since it can also show some degree of within-individual variability, particularly in humans; speech is essentially a rapid succession of fast changes of vocal tract shape that induce associated changes in formant frequencies. (Yet, individuals can be identified from sine-wave versions of their speech in which only formant frequencies are represented; Remez et al 1997). Modifications of formant frequencies by alteration of the vocal tract length-such as by protruding lips-have also been observed in non-human primates, although the range of formant variation (the 'vowel space') is much smaller in non-human primates than in humans (Lieberman et al 1969;Owren & Rendall 2003).…”
Section: Perception Of Identity Information In Voicementioning
confidence: 99%